Evaluation of TomoTherapy dose calculations with intrafractional motion and motion compensation. Issue 1 (3rd December 2017) - Chao, Edward H.; Lucas, Daniel; Schnarr, Eric
Abstract : Purpose: Anatomical motion, both cyclical and aperiodic, can impact the dose delivered during external beam radiation. In this work, we evaluate the use of a research version of the clinical TomoTherapy ® dose calculator to calculate dose with intrafraction rigid motion. We also evaluate the feasibility of a method of motion compensation for helical tomotherapy using the jaws and MLC. Methods: Treatment plans were created using the TomoTherapy treatment planning system. Dose was recalculated for several simple rigid motion traces including a 4 mm step motion applied either longitudinally or transversely, and a sinusoidal motion. The calculated dose volumes were compared to dose measurements that were performed by translating the phantom with the same motion traces used in the calculations. Measurements were made using film and ion chambers. Finally, the delivery plans were modified to compensate for the motion by sweeping the jaws for longitudinal motion and shifting the MLC leaves for transverse motion, and the calculations and measurements were repeated. Results: A transverse step motion shifted the dose that was delivered after the step occurred, but otherwise did not impact the dose distribution. Film measurements agreed with dose calculations to within 2%/2 mm for 99% of dose points within the 50% isodose line. A shift in the MLC leaf delivery pattern successfully compensated for the step motion to within the 3 mm accuracy allowed by the finite leaf widths. A longitudinal step motion impacted the dose in the interior of the target volume to a degree that was dependent on the planning field width and step size. Film measurements agreed with dose calculations to within 2%/2 mm for 98% of dose points within the 50% isodose line. Shifts in the jaw position successfully compensated for the longitudinal step motion. Sinusoidal (breathing‐like) motion was also studied, with similar results. Conclusions: A research version of the clinical TomoTherapy dose calculator has been shown to accurately calculate the dose from treatment plans delivered in the presence of arbitrary rigid motion. Modifications to the delivery plan using jaw and MLC leaf shifts that follow the motion can successfully compensate for the target motion.